Cryopreservation methods for in vitro potato crops: an overview - Amantaev, N.G. (Fundamental and Experimental Biology, 2022)
Potato is considered as one of the most important agricultural crops in the world. The genetic resources of potatoes (Solanum tuberosum L. ssp. tuberosum) and similar cultivated varieties are preserved by storing tubers or plants in vitro and cryopreservation. Arrays of worldwide scientific research centers utilizethe cryopreser-vation method to preserve plant genetic resources. It is used especially for those plants that are reproduced by vegetative method; it is impossible to preserve genetic identity of their material when propagating by seeds. Currently, international standards of gene banks have been developed (FAO, Gene bank Standards for Plant Genetic Resources for Food and Agriculture, 2014) for the long shelf life of samples of vegetative propagated plants and vegetable crops at ultra-low temperatures. These standards have been discussed by scientists from many countries in the world. It is connected with the fact that no cryopreservation methods are standardized for a particular plant object. Present overview provided information on various methods of cryopreservation of potatoes for long-term storage of the gene pool of vegetative reproduction. The most updated methods included quick–freeze: encapsulation-dehydration, vitrification, slow programmable freezing, encapsulation-vitrification, and droplet-vitrification. All these biotechnological methods made it possible to obtain healthy potato material, which was free from viral and fungal infections. They also facilitate to obtain test tube plants in large quantities, as well as to create large cryocollections of valuable forms of cultivated plant crops.